Business Performance Analysis Of Samba Lokan Oswari Food Using Balanced Scorecard - Kirana Chandra Putri; Reswita; M. Zulkarnain Yuliarso (Journal of Agri Socio Economics and Business, 2023)
Purpose of this study was to analysis the performance of Samba Lokan Oswari Food in Mukomuko Regency using the balanced scorecard methode based on four perspektives, namely financial perspective, custumer perspective, internal  business process perspective, and learning and growth perspective. Respondents in this study consisted of 1 business owner, 43 customers and 6 employees. The data used in this study are primary data obtained through interviews with business owners, customers and employees. And secondary data obtained from literature or previous research. The result showed that the business performance of Samba Lokan Oswari Food based on a financial perspective with a total score of 3, a custumer perspective with a total score of 1, an internal business process with a score of 1, and learning and growth perspective with a score of 2. Overall, the company value obtain Samba Lokan Oswari Foods business was 0.64. Based on the rating scale, the business performance of Samba Lokan Oswari Food was in the “good” category.